Study on the Various Geometry Configurations of a MicroChannel for Ammonia Synthesis - Mohd Amadin, Shafiq Iqbal (UNIVERSITI TEKNOLOGI PETRONAS, 2014)
The conventional method to produce ammonia employs the Haber-Bosch process at high pressure and temperature with aid of iron or iron oxide catalyst. These working conditions not only consumes tremendous amount of energy, it has higher safety risk, in addition to not achieving very high conversion and yield. OneBaja project offers a new method to synthesize ammonia which is via microreactor at ambient operating conditions with the aid of magnetic induction and facilitated by catalyst. Prior to study on microreactor, it is essential to understand the hydrodynamics of flow in microchannel. This study aims to investigate the hydrodynamics of the mixing of nitrogen and hydrogen gases in various geometry configurations of a microchannel in order to embed the catalyst for the ammonia synthesis at the uttermost optimum location. Computational Fluid Dynamics simulation will be employed to simulate the mixing of nitrogen and hydrogen gases whereby the results from will serve as a stepping point to design a microreactor for the ammonia synthesis.